Community Participation in Managing Waste and Waste Reduction Models in Baumata and Penfui Housing - Enni Rosida Sinaga; Albina Bare Telan; Siprianus Singga; Erika Maria Resi; I Made Sulistowati (Postgraduate, University of Mataram, 2023)
The aim of this study is to analyze the role and society in managing waste and reducing waste from households. This research is descriptive, describing the role and society in the management of household garbage, and further treating the role of the community in order to obtain the appropriate methods in reducing household waste. The subject of the study is a family member who has grown up one in each household of houses built by developers in the district of Naimata and Penfui of 72 houses. Role data collection and society, waste management, utilization and waste reduction by interviewing and observing, monthly waste data measured volume of waste referring to SNI 19-3964-1994 (2). The role as well as the society in the management of garbage which includes the category both 28% and not good 72%, the category of waste which includes 21% and is not good 79%, the society that exploits the waste 24% and does not exploit the waste 76%, which reduces the waste 22% and which does not reduce the waste 77%. The monthly amount of organic waste is 1 litre/day/house, and the monthly volume is 4 litres/house/day. From the results of FGD obtained waste management method is organic waste processed into compost, waste that has economic value given to the rulers and recycle. Results of crosstab roles as well as societies with waste management, waste utilization and waste reduction there is a correlation of roles and society in garbage management. The role as well as the society in managing garbage is still low, this affects the hygiene of the environment in which the waste is not properly managed can become a pathogen and become a source of infectious diseases and pollution to the environment.